Menakar Kesiapan Guru Madrasah Dalam Implementasi Kurikulum Merdeka - Yudha Andana Prawira; Firman Nugraha (Widyadewata, 2023)
This research was carried out based on doubts from several parties about the success of the implementation of the independent curriculum rolled out by the government. Therefore, researchers went into the field to dig data from the spearhead of curriculum implementation, namely madrasah and teachers. The study was conducted by descriptive method. The instruments used are interviews and open questionnaires. The resulting findings that have been analyzed by descriptive studies show that from the aspect of teachers, both the age and length of service of teachers stated that they were ready to implement an independent curriculum. Meanwhile, from the madrasah aspect, both the ibtidiyah, tsanawiyah, and aliyah madrasah levels, also stated that they were ready to implement an independent curriculum, even for the aliyah madrasah level, all subjects wanted this curriculum change.